A novel phospholipid delivery system of curcumin (Meriva®) preserves muscular mass in healthy aging subjects - Franceschi, F; Feregalli, B; Togni, S; Cornelli, U; Giacomelli, L; Eggenhoffner, R; Belcaro, G (European review for medical and pharmacological sciences, 2016)
Curcumin is known to interrupt pro-inflammatory signalling and increases anti-oxidant protection, thus inhibiting the expression of inflammatory cytokines and the expression and function of inducible inflammatory enzymes. Together, these effects contribute to limit the onset and the progression of sarcopenia, due to the major role played by inflammation in the pathophysiology of this disease. This registry study evaluates the effects of Meriva® supplementation in otherwise healthy elderly subjects. This was a registry, supplement study, conducted in healthy subjects > 65 years with apparent loss of strength and tiredness who freely decided to start one of the following interventions: (1) standard management (exercise, balanced diet including proteins) (n = 33); (2) standard management + Meriva® one tablet/day (n = 31); (3) standard management + Meriva® one tablet/day + other supplementation (n = 22). A number of functional and biochemical parameters were evaluated at baseline and after three months (hand grip, weight lifting, time/distance before feeling tired after cycling, walking and climbing stairs; general fitness, proteinuria, oxidative stress, Karnofsky scale; left ventricular ejection fraction). Significant improvements in all parameters, with respect to baseline values, were observed in the two supplementation groups (p < 0.05 for all comparisons). On the other hand, no improvement was observed in the standard management-only group. At three months, inter-group comparison revealed a statistical advantage in all parameters for both supplementation groups compared with the standard management-only group (p < 0.05 for all comparisons). Our registry study shows that the addition of Meriva® - either or not combined with other nutritional supplements - to standardized diet and exercise plan contributes to improve strength and physical performance in elderly subjects, potentially preventing the onset of sarcopenia.